Revisiting the scope of non-delegable duties of healthcare providers: issues and challenges - Jahn Kassim, Puteri Nemie; Ismail, Suzi Fadhilah; Azhar, Md Tahir (2014)

(untitled)
The doctrine of vicarious liability as developed under the common law imposes liability on the employers for negligence of their employees but not for independent contractors. As such, employers have become more and more creative in finding ways and methods to classify their staff as independent contractors in order to absolve themselves from legal responsibilities. Although various tests have been developed by the courts to distinguish between employees and independent contractors but in many occasions the distinction may not be so clear cut. However, even if the staff is classified as independent contractor, the courts have been prepared to extend the liability of the employer if the employer owes a non-delegable duty of care. Owing a non-delegable duty would mean that even though the performance of the duty is delegated to another, the responsibility on the manner in which the duty is performed still rests with the employer. In particular, a hospital or health service owes a non-delegable duty of care to their patients and such duty cannot be delegated to independent contractors. Nevertheless, the scope of non-delegable duties has not been particularly clear and precise and its development within the common law has been relatively rigid. Thus, there is a need for the scope and application of non-delegable duties to be developed through clear and comprehensive legislations, policies and guidelines so that healthcare providers can be clear that certain duties cannot be delegated even to a reputable contractor. As many contracted services directly affects patient care and are integral to their health and safety, healthcare providers must be clear on their responsibilities and constantly ensure that healthcare services are provided in a safe and effective manner. It is also within the notion of fairness and justice for the healthcare providers, who have benefited economically from their staff, to bear the corresponding losses as well.